Personality Of Tyler Hawkins In Alan Coulter's Remember Me Movie (2010): A Psychoanalytic Approach - NUGROHO., MUHAMMAD ARIF (2012)
The research is proposed to analyze the Personality of Tyler Hawkins in Remember Me Movie with Psychoanalytic Approach. There are two objectives: the first is to analyze the play in term of structural elements, and the second is to analyze the play based on Psychoanalytic Approach. This study is a descriptive qualitative study, using Remember Me Movie, and Tyler Hawkins as the major character is the object of analysis of the study. There are two kinds of data sources used in this analysis, namely primary and secondary. The primary data sources are the movie and script of the play itself and the secondary data sources are some books, internet and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the researcher employs descriptive qualitative analysis. The analysis is started by analyzing the structural elements of the movie. For the last, the researcher makes an analysis of Tyler Hawkins's id, ego, and superego. The researcher uses the theory of Psychoanalytic by Sigmund Freud because it is relevant to the problem. Based on the analysis, the outcome of this study shows that personality of the major character each caused problems and make a right decision quickly as a solution